VP66 Perception Of Decision Makers And Researchers Towards Health Technology Assessment In Ghana. (2017) - Addo, Rebecca; Hall, Jane; Goodall, Stephen; Haas, Marion
Abstract : INTRODUCTION: In recent years, the Ghana health system has been faced with the challenge of financial sustainability. New ways of making decisions in a cost-effective manner that ensure efficient use of available resources is being explored. Consequently, Ghana has been pursuing the formal introduction of Health Technology Assessment (HTA) for decision making in the health system. However, the limited use and impact of HTA on health systems has been associated with reasons including, and not restricted to, the knowledge and perception of decision makers towards it (1-3). Therefore as Ghana gears towards using HTA formally, it is important to assess the knowledge and attitude of potential users and producers of HTA. This will provide useful information for the setting up of an HTA agency. METHODS: A qualitative research approach using in-depth interviews was utilized. Twenty-three decision makers both at the national and district levels, and four researchers were interviewed. Thematic analysis was conducted using NVivo software. RESULTS: Only seven respondents had knowledge about HTA. Respondents perceived HTA differently, and the word 'technology', was often misconstrued as a device for communication such as mobile phone. Two main barriers to the use of HTA emerged; lack of resources (human, data, and finance) and politico-cultural issues. To address these barriers respondents recommended that stakeholders be involved in decisions concerning the guidelines for its conduct, composition of the appraisal team, and the focus of HTA. Generating of human, data and financial resources were also indicated. CONCLUSIONS: There is paucity of knowledge about HTA in Ghana. For Ghana to successfully introduce HTA for health decision making and realize its expected benefits, there will be a need to address the perceived barriers in a comprehensive manner. Also, to mitigate data and human resource barrier, Ghana will have to examine the available local data and human resource to build on.